2019
DOI: 10.21608/jpd.2019.42829
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Octacosanol Supplementation on Productive and Physiological Performance of Aged Silver Montazah Strain During Summer Season

Abstract: The objective of this study was to evaluate the impact of supplementation levels (0, 8, 16 and 24 mg octacosanol (octa) / kg diet) on productive and physiological performance of aged Silver Montazah strain. A total number of 120 laying hens and 24 cocks of Silver Montazah local strain at 60 weeks of age was utilized in a completely randomized design and randomly assigned into 4 treatment groups (30 hens + 6 cocks in each treatment). Each group was divided into three replicates (10 hens and 2 cocks in each repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 20 publications
2
0
0
Order By: Relevance
“…Serum concentrations of triglyceride and cholesterol of hens fed with 20 and 30 mg/kg of supplementary OCT were significantly ( p < 0.05) lower compared to those fed the control diet. Our results are consistent with previous reports that OCT supplementation lowers cholesterol and triglyceride concentrations in the blood serum of laying hens [ 12 , 18 ]. The reason for the reduction of cholesterol and triglycerides via supplementary OCT in laying hens is not well-understood, however it may be linked to OCT’s capacity to regulate enzymatic activity in the lipid metabolism [ 26 ].…”
Section: Resultssupporting
confidence: 94%
See 1 more Smart Citation
“…Serum concentrations of triglyceride and cholesterol of hens fed with 20 and 30 mg/kg of supplementary OCT were significantly ( p < 0.05) lower compared to those fed the control diet. Our results are consistent with previous reports that OCT supplementation lowers cholesterol and triglyceride concentrations in the blood serum of laying hens [ 12 , 18 ]. The reason for the reduction of cholesterol and triglycerides via supplementary OCT in laying hens is not well-understood, however it may be linked to OCT’s capacity to regulate enzymatic activity in the lipid metabolism [ 26 ].…”
Section: Resultssupporting
confidence: 94%
“…These results are supported by Peng et al [ 12 ], who showed that treatments containing 18 and 27 mg/kg of OCT significantly increased egg production. Similar outcomes were highlight by El-Wardany et al [ 18 ] and Long et al [ 10 ] following OCT treatment. OCT has been reported to elevate follicle stimulating hormone (FSH), luteinizing hormone (LH), estradiol (E2), and prostaglandin (P4) [ 10 ] involved in egg maturation and production.…”
Section: Resultssupporting
confidence: 85%